2020
DOI: 10.1371/journal.pone.0226122
|View full text |Cite
|
Sign up to set email alerts
|

Event timing in human vision: Modulating factors and independent functions

Abstract: Essential for successful interaction with the environment is the human capacity to resolve events in time. Typical event timing paradigms are judgements of simultaneity (SJ) and of temporal order (TOJ). It remains unclear whether SJ and TOJ are based on the same underlying mechanism and whether there are fixed thresholds for resolution. The current study employed four visual event timing task versions: horizontal and vertical SJ and TOJ. Binary responses were analysed using multilevel binary regression modelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
(168 reference statements)
0
1
1
Order By: Relevance
“…This might have first confused participants in their responses, but at the same time, left some room for performance improvement. In our Experiment 3, contrary to a comparable study by Arstila et al (2020), who found no learning due to a ceiling effect, we observed the disappearance of response bias across blocks of trials. The learning could be due to decreased thresholds for apparent motion.…”
Section: Discussioncontrasting
confidence: 99%
“…This might have first confused participants in their responses, but at the same time, left some room for performance improvement. In our Experiment 3, contrary to a comparable study by Arstila et al (2020), who found no learning due to a ceiling effect, we observed the disappearance of response bias across blocks of trials. The learning could be due to decreased thresholds for apparent motion.…”
Section: Discussioncontrasting
confidence: 99%
“…There is extensive literature regarding how visual and auditory information are integrated ( Colonius & Diederich, 2010 ;Kuling et al, 2013 ;Linares & Holcombe, 2014 ;Arstila et al, 2020 ). Desynchronization studies have been used to inspect when the relation is lost.…”
Section: Simultaneitymentioning
confidence: 99%